Breaching the Hyaluronan Barrier with PH20‐Fc Facilitates Intratumoral Permeation and Enhances Antitumor Efficiency: A Comparative Investigation of Typical Therapeutic Agents in Different Nanoscales. Issue 22 (27th September 2016) - Liu, Shan; Wei, Wei; Xie, Bo; Yue, Hua; Ni, Dezhi; Bao, Yali; Ma, Guanghui; Su, Zhiguo G.
Abstract : In contrast to traditional strategies based on external driving forces, an internal path for intratumoral delivery is explored by degrading the tumor microenvironment component hyaluronan. Natural hyaluronidase PH20 and constructed long‐acting PH20‐Fc have been used to achieve this objective. It has been then evaluated how these agents facilitate the diffusion of the following typical therapeutic agents varying in nanoscales: doxorubicin (≈1.5 × 1.0 × 0.7 nm) chemotherapy, trastuzumab (10–15 nm) biotherapy, and gold nanorod (≈100 × 35 nm) thermotherapy. In traditional 2D cultures, PH20 and PH20‐Fc have little influence on cytotoxicity due to lack of a tumor microenvironment. However, the cytotoxicities of the three therapeutic agents in 3D tumor spheroids are all enhanced by PH20 or PH20‐Fc because hyaluronan degradation facilitates therapeutic penetration and accumulation. Furthermore, in vivo evaluations reveal that the significantly prolonged circulation time of PH20‐Fc leads to accumulation in the tumor and subsequent hyaluronan degradation. Consequently, PH20‐Fc coadministration further inhibits tumor growth. The performance of PH20‐Fc varies for the three therapeutic agents due to their different nanoscales. Trastuzumab benefits most from combination with PH20‐Fc. The results provide here novel insights that can aid in the development of more effective hyaluronidase‐based therapeutic systems. Abstract : Intratumoral delivery of typical therapeutic agents (doxorubicin, trastuzumab, and pegylated gold nanorods) can be significantly enhanced by degrading tumor microenvironment component hyaluronan with long‐acting hyaluronidase PH20‐Fc. Meanwhile, the performance of PH20‐Fc varies among these three therapeutic agents due to ther different nanoscales, and Tmab benefits most in penetration and accumulation.